BIOACTIVITY OF OCIMUM AMERICANUM L. ESSENTIAL OILS AGAINST FOUR INSECT PESTS OF STORED FOOD COMMODITIES - Ogendo, J. O.; Deng, A. L.; Kostyukovsky, M.; Ravid, U.; Matasyoh, J. C.; Omolo, E. O.; Kariuki, S. T.; Kamau, A. W.; Shaaya, E. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Laboratory studies were conducted to evaluate the fumigant and repellent properties of Ocimum americanum L. essential oils against adult Sitophilus oryzae L., Rhyzopertha dominica F., Tribolium castaneum (Herbst) and Callosobruchus chinensis F. Each essential oil was tested at four (0, 1, 5, 10 Âµl/L air) and five (0, 0.5, 1.0, 1.5, 2.0 Âµl oil/ g grain) rates in space fumigation and choice bioassay studies, respectively, with four replicates per treatment. Corrected percent mortality and PR were arcsine transformed before ANOVA and means separated by Tukey’s HSD test [1, 2]. Dose-responses were further subjected to Probit analysis and LC50 values computed [3]. Leaf essential oil at 10 Âµl/L air 24 h after treatment, caused 88.8, 87.5, 11.3 and 100% adult mortality of S. oryzae, R. dominica, T. castaneum and C. chinensis, respectively (LC50 values of 0.38, 0.49, NS and 0.18 Âµl/L air, respectively). The LC50 values varied with plant part assayed. Leaf essential oil was most efficacious (LC50 values: 0.18-0.49 Âµl/L air) followed by fruit (1.15-15.07 Âµl/L air) and stem (3.70-34.68 Âµl/L air) essential oils, respectively. In the choice bioassay studies, fruit essential oil (at 2.0 Âµl oil/ g grain and 24 h) produced highest PR values of 81 and 94% against S. oryzae and R. dominica, respectively. Similarly, the leaf oil repelled 51 and 83% of T. castaneum and C. chinensis, respectively. Clear intra-species variations in essential oil compositions and inter-insect species differences form the basis of differential bioactivity observed. Leaf oil was high in monoterpenes whereas stem and fruit oil were high in sesquiterpenes. Results show that plant volatiles are potential alternative grain fumigants and further validation studies required for compatibility with tropical agriculture. Refrerences: [1] Rajendran, S. and Muralidharan, N. Effectiveness of allyl acetate as a fumigant against five stored grain beetle pests. Pest Management Science 61: 97-101 (2005). [2] Rozman et al. Toxicity of naturally occuring compounds of Lamiaceae and Lauraceae to three stored-product insects. Journal of Stored Products Research 43(4): 347-355 (2007). [3] Finney, D.J. Probit Analysis, 3rd ed. Cambridge Univ. Press, London (1971).